Differences of anteroposterior facial dimensions in male and female children on intermediate mixed and early permanent dentition using Cervical Vertebrae Maturation Index - Listania, Ica; Kuswandari, Sri; Mahendra, Putri Kusuma Wardani (Faculty of Dentistry Universitas Padjadjaran, 2021)
Introduction: Cervical vertebrae are one of the indicators for craniofacial bones maturation. Timing of craniofacial bone maturation determined achievement of orthodontic early treatment. Some previous researchers recommended cervical vertebral maturation to assess craniofacial growth. This study was aimed to analyse the differences of anteroposterior facial dimensions in male and female children on intermediate mixed and early permanent dentition using Cervical Vertebrae Maturation Index (CVMI). Methods: An analytic observational study with a cross-sectional design was conducted on the students of Islamic Elementary School (Madrasah Ibtidaiyah) in Depok district, Sleman, Yogyakarta, from July 2019 to January 2020. Subjects consisted of 22 males and 22 females aged 8-11 years, obtained by a consecutive sampling technique. The anteroposterior facial analysis was performed on the lateral cephalometry for measuring the distance of Sella turcica to Nasion (S-N) representing the anterior cranial base, Posterior Nasal Spine to Anterior Nasal Spine (PNS-ANS) representing the maxilla and Gonion-Menton (Go-Me) and Condylion-Gnathion (Co-Gn) represents the mandible. Assessment of CVMI was decided by the Hassel and Farman methods. Data were analysed by One Way ANOVA. Results: The mean value of S-N, PNS-ANS, Go-Me, and Co-Gn dimensions, generally were higher in males than females; however, only dimensions of maxillary and mandibular were showed significant difference (p<0.05), while the S-N dimension was not significantly different (p>0.05). At the interval of CVMI 3 and 4, the Go-Me and Co-Gn dimensions showed a significant difference (p<0.05) both in males and females. Conclusion: There was a difference in anteroposterior dimensions of the maxillary and mandibular in cervical vertebral maturation in children with intermediate mixed and early permanent dentition, however, no difference was found in the anterior cranial base.